Real-world long-term outcomes in multiple myeloma with VRD induction, Mel200-conditioned auto-HCT, and lenalidomide maintenance. Issue 3 (23rd February 2022) - Gaballa, Mahmoud R.; Ma, Junsheng; Tanner, Mark R.; Al-Juhaishi, Taha; Bashir, Qaiser; Srour, Samer A.; Saini, Neeraj Y.; Ramdial, Jeremy L.; Nieto, Yago; Murphy, Regan; Rezvani, Katayoun; Tang, Guilin; et al.
Abstract: Standard-of-care for newly-diagnosed, autologous hematopoietic stem cell transplantation (auto-HCT)-eligible, multiple myeloma (MM) patients includes bortezomib, lenalidomide, and dexamethasone (VRD) induction followed by melphalan 200 mg/m 2 (Mel200)-conditioned auto-HCT and lenalidomide maintenance. We completed a retrospective case series assessing outcomes of 187 MM patients who received this regimen at our institution. The 100-day non-relapse mortality incidence was zero. Before auto-HCT, 9.6 and 52.9% of patients achieved a complete response (CR) or ≥ very good partial response (VGPR), respectively. At day-100 post-transplant, 29.4 and 74.9% had achieved a CR/stringent-CR (sCR) or ≥ VGPR, respectively. At the last evaluation, 57.2% of patients had CR/sCR and 87.1% had ≥ VGPR. Median follow-up, progression-free survival (PFS), and overall survival (OS) were 63.2, 50, and 101.7 months, respectively. The 5-year PFS and OS were 43.1 and 79%. High-risk cytogenetics was associated with worse outcomes. This study illustrates that VRD induction, Mel200-conditioned auto-HCT, and lenalidomide maintenance are associated with good outcomes in MM.